2022
DOI: 10.1002/hrdq.21493
|View full text |Cite
|
Sign up to set email alerts
|

Measures of climate for inclusion and diversity: Review and summary

Abstract: The purpose of this study was to review diversity climate and inclusive climate scales and identify their features. By using three key concepts present in the diversity and inclusion climate literature (fairness, uniqueness, and belongingness), 13 measures were analyzed and summarized according to individual, group, leadership, and organizational levels. Both inclusive and diversity climate measures are based on the assumption that individual differences should be perceived, accepted, and valued in organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Even police officers in law enforcement roles identified that building trust and connections were key to building inclusiveness. This paper's conceptualization of the climates of diversity and inclusivity is different from other studies which highlight dimensions such as group involvement, the ability to influence decisions, and access to information and resources (Mor Park et al 2022). Other defined dimensions include equitable employment practices, the integration of differences with regard to working in a non-threatening environment where people can reveal their "true" selves, and inclusion in the decision-making process where employees feel as though their diverse perspectives are valued and sought after (Nishii 2013).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Even police officers in law enforcement roles identified that building trust and connections were key to building inclusiveness. This paper's conceptualization of the climates of diversity and inclusivity is different from other studies which highlight dimensions such as group involvement, the ability to influence decisions, and access to information and resources (Mor Park et al 2022). Other defined dimensions include equitable employment practices, the integration of differences with regard to working in a non-threatening environment where people can reveal their "true" selves, and inclusion in the decision-making process where employees feel as though their diverse perspectives are valued and sought after (Nishii 2013).…”
Section: Discussionmentioning
confidence: 78%
“…The results in this study provide a different framework for defining an inclusive climate amongst minorities and indigenous people. The concepts relied upon openended interviews and inductive processes that concerned defining concepts and measures that reflected contexts, rather than deductive processes, as illustrated in other studies (Nishii 2013;Park et al 2022). In this study, possible concepts and measures that could define inclusiveness for minorities and Indigenous people are as follows: (i) leadership practices supporting inclusiveness within the organization; (ii) leadership engaging in the community and becoming community-centered; (iii) multicultural practices as a foundation for defining diversity; and (iv) relational practices engaging with and involving staff.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In sum, these findings offer support for the relationship between decentralization and important outcomes like DEI. For example, Park et al (2022) recently reviewed and recommended measures pertaining to climates that include DEI. Some of the recommended measures included and emphasized fairness, relationships, and interpersonal interactions.…”
Section: Centralizationmentioning
confidence: 99%